PEMBUATAN APLIKASI E-TATIB BERBASIS ANDROID MENGGUNAKAN BAHASA PEMROGRAMAN DART: MAKING AN ANDROID-BASED E-TATIB APPLICATION USING THE DART PROGRAMMING LANGUAGE - Isa Faqihuddin Hanif; Ghifar Marhaban Sinambela (Jurnal Teknologi dan Terapan Bisnis, 2021)
An automatic application of discipline is needed in schools to achieve the school's vision and mission. The research method used in developing this application is the Waterfall method. The reason for using this method is because the Waterfall method has a sequential model, so that developers can start doing research until testing is more neat and structured. And this method can easily make improvements if the stage that is being worked on has an error gap. The design of the e-Tartib application itself is designed on an android mobile basis. The programming language used is the Dart language which is included in the Flutter SDK with the MySQL Database. The e-Tartib application is designed to minimize violations committed by students and can record student violations that are integrated and stored neatly. The expected results in this study are that later this e-Tartib application will enable students to understand and follow school rules or regulations so that teaching and learning activities will run optimally. This research was conducted at SMK Bina Citra Asia Jakarta.